Distribution of wild boar (Sus scrofa) damage and harvest loss in crop fields - Lindblom, Sofie (2011)
The last decades the populations of wild boar (Sus scrofa) has increased rapidly over the species’ entire European range, including Sweden. This is followed by increasing human-wildlife conflicts as a result of the wild boar foraging behavior, causing damage to agricultural crop fields due to trampling and feeding. To be able to minimize damage we need more knowledge of where in the fields the risk of damage is high and what features in the landscape that affect this risk. I analyzed damage distribution in relation to the distance to six different landscape features; forest, road, ditch, building, game field and bait station, in the study area, the Island Mörkö in eastern central Sweden. A binary logistic regression analysis showed that damage increased with proximity to forest, road, ditch and bait station, strongest affected by the distance to forest and bait station. The damage also showed to be more severe closer to the forest edge. I also calculated the cost of wild boar damage, during the harvest season of 2010, based on the field survey. The apparent income loss due to damaged and reduced harvest in wheat, oats and barley fields was this year about 120 000 SEK. This sum indicates a significant problem and point at the need for measures to minimize damage. My results suggest, for example, that sensitive crops like wheat should be cultivated on fields with less edge towards the forest, and that bait stations should be placed as far away from fields as possible.